Does Orexin B-Binding Receptor 2 for Orexins Regulate Testicular and Epididymal Functions in Normal and Cryptorchid Dogs? - Squillacioti, Caterina; Pelagalli, Alessandra; Assisi, Loredana; Costagliola, Anna; Van Nassauw, Luc; Mirabella, Nicola; Liguori, Giovanna (Frontiers in Veterinary Science, 2022)
Orexins A (OXA) and B (OXB) and the receptors 1 (OX1R) and 2 (OX2R) for orexins are hypothalamic peptides found in several mammalian organs and participated to the control of a wide assortment of physiological and pathological functions. The distribution of OXA and OX1R has been extensively studied in the male gonad of mammals. Here, we examined the expression and localization of OXB and OX2R as well as their possible involvement in the regulation of testicular and epididymal functions, in healthy and cryptorchid dogs, employing some techniques such as immunohistochemistry, Western blotting, and real-time RT-PCR. In vitro tests were also carried out for evaluating the steroidogenic effect of OXB. OXB and OX2R were expressed in spermatocytes, spermatids, and Leydig cells in normal testis. Their localization was restricted to Sertoli and Leydig cells in cryptorchid conditions. OXB was found to be localized in all tracts of both normal and cryptorchid epididymis, whereas OX2R was found only in the caput. Because the small molecular weight of the peptides OXA and OXB, the expression of their precursor prepro-orexin (PPO), OX1R, and OX2R proteins and mRNAs were investigated by means of Western blot and real-time RT-PCR analyses, respectively in all tested groups of. In particular, the mRNA level expression of all three genes was higher in cryptorchid dogs than in normal ones. In vitro tests demonstrated that OXB—by binding OX2R—is not involved in testicular steroidogenic processes. Therefore, the findings of this study might be the basis for further functional and molecular studies addressing the possible biochemical effects of OXB and OX2R in normal and pathological conditions of the male reproductive system.